1995
DOI: 10.1093/hmg/4.9.1629
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of a distal form of spinal muscular atrophy with upper limb predominance to chromosome 7p

Abstract: An autosomal dominant distal form of spinal muscular atrophy mainly affecting the upper limbs with a mean age of onset of 17 years has been identified in a large Bulgarian family. Linkage of the above family to the spinal muscular atrophy type I, II and III locus on chromosome 5 has been excluded. In an attempt to map this disease gene we have analysed individuals of this family, with more than 140 microsatellite polymorphic markers of the human genome. A maximum lod score of 5.99 at theta = 0.007 has been obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 0 publications
1
56
0
1
Order By: Relevance
“…In addition, we showed that both conditions are genetically heterogeneous, as some individuals with each phenotype do not carry a BSCL2 mutation. Also, the originally described dHMN-V phenotype 12 (also called distal spinal muscular atrophy V and CMT 2D), which has already been associated with mutations in the gene glycyl-tRNA synthetase 13 (GARS; OMIM #600794), supports the presence of genetic heterogeneity. Further genotype-phenotype studies are needed to find out whether the distinct phenotypes correlate with specific mutations and to establish whether there are phenotypically different forms of dHMN-V caused by mutations in BSCL2 versus GARS.…”
Section: Distal Hereditary Motor Neuropathy (Dhmn) or Distal Spinal Mmentioning
confidence: 89%
“…In addition, we showed that both conditions are genetically heterogeneous, as some individuals with each phenotype do not carry a BSCL2 mutation. Also, the originally described dHMN-V phenotype 12 (also called distal spinal muscular atrophy V and CMT 2D), which has already been associated with mutations in the gene glycyl-tRNA synthetase 13 (GARS; OMIM #600794), supports the presence of genetic heterogeneity. Further genotype-phenotype studies are needed to find out whether the distinct phenotypes correlate with specific mutations and to establish whether there are phenotypically different forms of dHMN-V caused by mutations in BSCL2 versus GARS.…”
Section: Distal Hereditary Motor Neuropathy (Dhmn) or Distal Spinal Mmentioning
confidence: 89%
“…All family members were genotyped at 138 STR markers from the Research Genetics Screening set 4A, using previously described methodology (Christodoulou et al, 1995). Refined mapping was performed with more dense STR markers selected from candidate regions.…”
Section: Genome-wide Screening Homozygosity Mapping and Linkage Analmentioning
confidence: 99%
“…dSMA-V, a neuromuscular disorder, is an axonal neuropathy characterized by impaired motor function and the absence of sensory loss in the extremities compared with CMT2D (Antonellis et al 2003;Barisic et al 2008). Both CMT2D and dSMA-V manifest as severe phenotypes in the upper extremities (Christodoulou et al 1995;Sambuughin et al 1998). Multiple GARS mutations have been identified in patients with these diseases: A57V, E71G, L129P, G240R, P244L, I280F, H418R, D500N, G526R, S581L and G598A (Christodoulou et al 1995;Ionasescu et al 1996;Sambuughin et al 1998;Antonellis et al 2003;Sivakumar et al 2005;Del Bo et al 2006;James et al 2006;Rohkamm et al 2007; Abe & Hayasaka 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple GARS mutations have been identified in patients with these diseases: A57V, E71G, L129P, G240R, P244L, I280F, H418R, D500N, G526R, S581L and G598A (Christodoulou et al 1995;Ionasescu et al 1996;Sambuughin et al 1998;Antonellis et al 2003;Sivakumar et al 2005;Del Bo et al 2006;James et al 2006;Rohkamm et al 2007; Abe & Hayasaka 2009). L129P, H418R and G526R are involved only in dSMA-V and G240R, P244L and I280F are involved only in CMT2D, but E71G and D500N are involved in either CMT2D or dSMA-V (Christodoulou et al 1995;Ionasescu et al 1996;Sambuughin et al 1998;Antonellis et al 2003;Sivakumar et al 2005;Del Bo et al 2006;James et al 2006;Rohkamm et al 2007;Abe & Hayasaka 2009). Most of dSMA-V-or CMT2D-associated mutations have a range of effects on dimer interactions, whereas L129P and G240R GARS mutations have less capacity to form dimer (Nangle et al 2007).…”
Section: Introductionmentioning
confidence: 99%